Site specific response spectrum acceleration due to Sumatran earthquake: Science and Technology Complex, UiTM Shah Alam / Ahmad Fahmy Kamarudin - Kamarudin, Ahmad Fahmy (2006)
Peninsular Malaysia lies in a low seismic region. However, distant earthquake from Sumatran subduction zone (SSZ) and Sumatran great fault zone have frequently shaken existing structure especially in the metropolis cities where a large concentration of low rise, medium rise and high rise reinforced structure can be found. The safety of these building was impugned as most of the building were designed according to BS 8110 which has no seismic provision.